Logical fallacy in speakers’ arguments: what do we learn from final round debate of NUDC - Agustin, Karina Estiani; Triana, Novita; -, Nasrullah (Universitas Lambung Mangkurat, 2024)
In debate, speakers often employ logical fallacies to bolster their statements in order to secure victory by persuasively introducing a collection of factual or belief errors. Numerous studies have analyzed the use of logical fallacies, primarily in presidential debates and public figures’ speeches. However, there has been limited research specifically investigating the logical fallacies in students' debates. Therefore, this research aimed to examine the arguments presented by the speakers in the final round debate at NUDC. The objective is to identify and categorize the logical fallacies present in the arguments. The study employed descriptive-qualitative method. The data was taken from recorded video and transcript of the argument featuring eight speakers among NUDC’s finalists. The data are reduced and organized into arguments containing only logical fallacies. They are classified into Damer’s category of arguments. The study reveals that eight fallacies were identified. The most prevalent types of fallacies were those that violated the relevant criterion. Meanwhile, the most frequently occurred fallacy types are manipulation of emotion, appeal to common opinion, and causal oversimplification. The findings suggest that students should be taught to construct effective arguments that are based on evidence and logic, rather than relying on emotional appeals or popular opinions.